Uji Seakeeping Model Kapal Displacement pada Area Terbuka - Andreas, Mario; Poundra, G.A.P.; Munazid , Ali; Hardianto, Didik; Suwasono, Bagiyo (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Ship Movement is an important factor in shipbuilding. In determining the ship's maneuverability, there are many aspects that must be considered in the design, namely resistance and angle of attack of the waves. In determining the angle of attack of the waves, the test uses the trigonometry principle to determine the angle of attack of the waves. Where the results of the 3 maneuvers of the Heave, Roll and Pitch ships at speeds of 0 knots, 0.389 knots, 0.778 knots, 1.166 knots, 1943 knots, it is known that the displacement model ship can be used in an open area with a set scale.